Program Penerapan New Normal (Normal Baru) Melalui Edukasi Kesadaran Masyarakat Terhadap Pencegahan Covid-19 di kecamatan Simpang Kanan - Jesi Alexander Alim; Meza Mardita Meza; Melvi Lesmana; Agus Sulastio; Ika Nuansa Fitri; Nurlita Nurlita; Aris Tarmizi; Naila Fauza (Journal of Community Engagement Research for Sustainability, 2021)
Covid-19 is caused by the (SARS-CoV-2) which attacks the respiratory system. WHO has declared Covid-19 a pandemic. Kukerta is a form of community service activity. One type of Kukerta during this pandemic is the Covid19 volunteer Kukerta. In the COVID-19 volunteer Kukerta activity held in Simpang Kanan District, the first step taken by Kukerta students was to analyze the situation in the field. The purpose of the volunteer work program is to prevent the spread of Covid-19 in the Simpang Kanan district by educating the public about the dangers of Covid-19. The steps of the activities carried out are: (1) Public education about the New Normal; and (2) Covid-19 prevention program. The achievement measurement tool used is in the form of outputs that have been done in the form of logbooks, youtube, and social media publications. The results of the activity were the implementation of several programs such as spraying disinfectants, collecting data on people under monitoring, distributing masks, making and distributing Hand Sanitizers, socializing the New Normal, providing hand washing facilities, demonstrations on making Hand Sanitizer and appropriate technology.